Recurrent humid phases in Arabia over the past 8 million years - Monika Markowska; Hubert B. Vonhof; Huw S. Groucutt; Paul S. Breeze; Nick Drake; Mathew Stewart; Richard Albert; Eric Andrieux; James Blinkhorn; Nicole Boivin; Alexander Budsky; Richard Clark-Wilson; et al. (Nature, 2025)
Abstract The Saharo-Arabian Desert is one of the largest biogeographical barriers on Earth, impeding dispersals between Africa and Eurasia, including movements of past hominins. Recent research suggests that this barrier has been in place since at least 11 million years ago1. In contrast, fossil evidence from the late Miocene epoch and the Pleistocene epoch suggests the episodic presence within the Saharo-Arabian Desert interior of water-dependent fauna (for example, crocodiles, equids, hippopotamids and proboscideans)2–6, sustained by rivers and lakes7,8 that are largely absent from today’s arid landscape. Although numerous humid phases occurred in southern Arabia during the past 1.1 million years9, little is known about Arabia’s palaeoclimate before this time. Here, based on a climatic record from desert speleothems, we show recurrent humid intervals in the central Arabian interior over the past 8 million years. Precipitation during humid intervals decreased and became more variable over time, as the monsoon’s influence weakened, coinciding with enhanced Northern Hemisphere polar ice cover during the Pleistocene. Wetter conditions likely facilitated mammalian dispersals between Africa and Eurasia, with Arabia acting as a key crossroads for continental-scale biogeographic exchanges.